2010
DOI: 10.1111/j.1365-2702.2010.03320.x
|View full text |Cite
|
Sign up to set email alerts
|

The predictors of adopting a health‐promoting lifestyle among work site adults with prediabetes

Abstract: Findings guide the clinical assessment (e.g. self-efficacy) of prediabetic adults regarding their health-promoting lifestyles and provide effective guidelines for designing lifestyle interventions to prevent prediabetes in high-risk groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 24 publications
4
22
0
Order By: Relevance
“…Perceived benefits/barriers to exercise were measured using an 8-item and 7-item scale respectively adopted from Chen and Lin (2010). Subjects were asked to rate their beliefs on benefits/barriers of the health action on a five-point Likert scale (1="strongly disagree to 5= "strongly agree").…”
Section: Predictorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived benefits/barriers to exercise were measured using an 8-item and 7-item scale respectively adopted from Chen and Lin (2010). Subjects were asked to rate their beliefs on benefits/barriers of the health action on a five-point Likert scale (1="strongly disagree to 5= "strongly agree").…”
Section: Predictorsmentioning
confidence: 99%
“…The original study reported Cronbach's alphas ranging from 0.90 to 0.95 for the original scales, whereas Cronbach's alpha of 0.79 to 0.87 was achieved in the present study, demonstrating good internal consistency of this instrument. Perceived self-efficacy was assessed by the Chinese version (Chen & Lin, 2010) of the self-rated abilities scale originated by Becker, Stuifbergen, Oh, and Hall (1993). Self-efficacy of exercise and diet management was measured on 7-item and 6-item subscales respectively using a five-point Likert scale (from 1="no confidence" to 5="100% confidence").…”
Section: Predictorsmentioning
confidence: 99%
“…state that different ethnic groups need to have different interventions to modify behaviour. Self‐efficacy underpins an individual's ability to then make changes to their lifestyle . However, even with this understanding, ambivalence was one of the underpinning themes found in the studies .…”
Section: Resultsmentioning
confidence: 99%
“…The evidence demonstrated that lack of knowledge and understanding about pre‐diabetes on diagnosis resulted in patients not recognising the importance of lifestyle changes even though there is a strong correlation between knowledge of pre‐diabetes and adoption of healthy lifestyles …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation